Digital dichotomous key in botanical education of pupils in primary school - Branko V. Anđić; Stanko M. Cvijetićanin, Мirjana T. Maričić; Danijela D. Stešević (University of Belgrade, Teacher Education Faculty, 2019)
Traditional teaching, which is predominantly represented in the teaching of biology in primary and secondary schools, is one of the main reasons for the emergence of the plant blindness among students. Modernization of teaching methods could reduce this phenomenon among students. The aim of the research is to examine the contribution of the created digital dichotomous key (DDK) and instructive (traditional) methods to the quality and durability of eighth-grade students' knowledge of the Systematics and Classification of Plants. The research also examines the students' opinion on the contribution of DDK to their knowledge and motivation for learning botanical contents. The research involved the participation of one hundred twenty students of the eighth grade from Montenegro (12- 13 years old), who were divided into two groups: K (contents were taught by IM) and E (the same contents were taught by DDK). The quality of students' knowledge after content realization was tested with post-test, while the durability of knowledge was tested by the retest. Students opinions are examined by the survey. The results of the research showed that DDK contributed to the higher quality and durability of students' knowledge in relation to IM at cognitive levels: analysis, evaluation, and synthesis. Sstudents of the E group have a positive opinion on the contribution of the DDK to the quality of their botanical knowledge and a greater motivation for studying the plant world. In the realization of the aforementioned botanical contents, priority should be given to DKK in relation to IM.